Study on the interaction between CLT structural elements and the Icelandic climate - Filippo Riviera 1991- (2021)
In the strive for sustainability, architects and engineers must aim to improve the environmental impact of the building sector. Engineering wood products (EWP), such Cross-Laminated Timber (CLT) technology, are a sustainable alternative to concrete and steel in many construction projects. Some of the uncertainties for the implementation of CLT are linked to the moisture behaviour, the airtightness of the elements after wetting and drying cycles, the use or non-use of vapour barrier on the wall assembly, and the air tightness during dimensional changes. Climatic conditions greatly influence the behaviour and applicability of CLT, so that tailored adaptations to specific environment are often required. The primary aim of the current research is to study the behaviour of a CLT construction in the Reykjavik area, and any possible climatic influence, with the intentions to provide the building industry with new data and improved knowledge. A second aspect is to investigate the mould growth potential on CLT samples that have been subjected to varying degree of moisture under controlled conditions at the Icelandic Innovation Center. The samples are supposed to correspond to the design, construction process, and operational life of a CLT building in Iceland. Moisture management is found to be essential for the quality of the structure itself, and for the wellbeing of the inhabitants. The performance of CLT is observed to be related to the number of layers, where CLT components with more than 3 layers generally perform better regarding moisture transportation, fire safety, and airtightness requirements. It is recommended that CLT structural elements should not be exposed, at any time, to direct contact with precipitation. As water absorption in CLT elements can lead to unforeseen mould growth and structural decay. The best practise for CLT construction is to plan a moisture safe environment for the duration of the construction period utilizing available protection membranes. To perform periodic moisture measurements ...